2018
DOI: 10.1002/asl.862
|View full text |Cite
|
Sign up to set email alerts
|

Can coupled models perform better in the simulation of sub‐seasonal evolution of the western North Pacific subtropical high than atmospheric models in boreal summer?

Abstract: This study examines the climatological sub‐seasonal evolution of the western North Pacific subtropical high (WNPSH) in boreal summer using observation and multiple state‐of‐the‐art climate models, which has not been focused by previous research. The two sub‐seasonal shifts in boreal summer are analyzed, one from June to July (J–J) and another from July to August (J–A). In observation, the WNPSH consistently retreats eastward and jumps northward (weakens) from June to August. Driven by observed sea surface temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…This relation between the local SST anomaly and circulation indicated that it was the shift in the circulation that induced the relative warming/ cooling of the local SST from early to late summer, which further confirmed the importance of the local air-sea interactions in this region. In our previous work, we found that compared with the atmosphere-only models, the air-sea coupled models could perform much better in simulating the month-to-month variation in the WNPSH in the boreal summer (Dong et al, 2017a(Dong et al, , 2017bLin et al, 2018). Similar results can be derived from the composite of the ERA-Interim and NCEP1 datasets (Figures 10 and 11).…”
Section: Relationship With Ocean Signalssupporting
confidence: 66%
“…This relation between the local SST anomaly and circulation indicated that it was the shift in the circulation that induced the relative warming/ cooling of the local SST from early to late summer, which further confirmed the importance of the local air-sea interactions in this region. In our previous work, we found that compared with the atmosphere-only models, the air-sea coupled models could perform much better in simulating the month-to-month variation in the WNPSH in the boreal summer (Dong et al, 2017a(Dong et al, , 2017bLin et al, 2018). Similar results can be derived from the composite of the ERA-Interim and NCEP1 datasets (Figures 10 and 11).…”
Section: Relationship With Ocean Signalssupporting
confidence: 66%
“…The water vapor budget analysis confirmed that the precipitation increase can be mainly attributed to the vertical motion change from July to August. In a previous study [30], CMIP5 AMIP simulations were examined and the results show that they cannot reasonably reproduce the precipitation increase from July to August, which is associated with the local SST change, as discussed in the previous subsection. The eastward retreat of the WPSH cannot be reproduced by AMIP experiments [29].…”
Section: Cmip6 Simulationsmentioning
confidence: 98%
“…The climatological precipitation change from June to July and from July to August, along with the simulation performances in the uncoupled Atmospheric General Circulation Model (AGCM) and coupled CMIP5 models, have been examined in a previous study [30]. The author found that from June to July, the local SST increases, thus in AGCMs the positive precipitation center can be reproduced very well.…”
Section: Observationmentioning
confidence: 99%
See 2 more Smart Citations